Nomenclatural and taxonomic notes on Vismia (Hypericaceae) - Shimizu, Gustavo Hiroaki; Martins, Milena Ventrichi; Bittrich, Volker; Amaral, Maria Do Carmo Estanislau Do (Phytotaxa, 2024)
Vismia is a neotropical genus and in Brazil it is currently represented by 30 species. Along with the study of the species that occur in this country, we assessed the nomenclatural questions involved with their names, and a first part of these results are presented. Twelve lectotypes, including one as a second-step, were designated for correct names and synonyms associated with eleven species of Vismia. Furthermore, we provided additions and corrections to the collection data, and nomenclatural comments for each species. Here we also reduce V. parviflora to a synonym of V. micrantha, based on morphological characters.